Pengaruh Work Family Conflict dan Stres Kerja Terhadap Kinerja Karyawan PT. BPR Syari’ah Lantabur Tebuireng Jombang - Umdatul Fadhilah (BIMA : Journal of Business and Innovation Management, 2020)
Family conflict and work stress on the performance of the employees of PT. BPR Syari’ah Lantabur Tebuireng Jombang. The method used in this research is quantitative research methods using causal research methods. The result showed that: (1) Work family conflicts are not partial to the perfomance of employees of PT. BPR Syari’ah Lantabur Tebuireng Jombang, (2) Job stress does not require partial impact on the performance of employees of PT. BPR Syari’ah Lantabur Teburieng Jombang, (3) Working family conflicts and work stress are not simultaneous with the performance of the employees of PT. BPR Syari’ah Lantabur Tebuireng Jombang.